Perception-action coupling during discriminative interceptive actions - Sun, Yu; Jang, Dukchan; Park, Sangbum (Frontiers in Psychology, 2025)
IntroductionInterception is a complex task that requires the integration of perception and action under temporal constraints. Decision-making about whether to respond to moving stimuli involved in discriminative responses may further increase the cognitive load imposed on the performer, influencing perception-action coupling during interception. This study investigated the effects of discriminative response requirements on eye and hand movements, the coupling of perception and action, and the accuracy of responses during interceptive actions.MethodsTwelve right-handed male participants performed interceptive actions to stimuli moving at three velocities (0.53 m/s, 0.66 m/s, 0.88 m/s) in discriminative (target-specific) and non-discriminative (target non-specific) conditions. While the non-discriminative condition required participants to respond to presented stimuli in all trials, the discriminative condition required them to respond to the stimulus moving toward a pre-defined target area.ResultsTiming errors were greater in the discriminative condition than the non-discriminative condition, and increased with increasing stimulus velocity. Both reaction and movement times decreased with increasing stimulus velocity, and the reaction times were longer in the discriminative condition than the non-discriminative condition. Variables representing the temporal aspects of interceptive actions, including saccadic latency, saccadic frequency, gaze duration, and temporal coupling of gaze and stimulus decreased with increasing stimulus velocity. Compared to the non-discriminative condition, saccadic frequency was higher, gaze duration was shorter, and the temporal coupling of gaze and stimulus was longer in the discriminative condition. Variables representing the spatial aspects of responses, including radial error, gaze error, and the spatial couplings of gaze and hand, however, remained unaffected by task conditions.ConclusionThese findings suggest that decision-making about whether to respond to moving stimuli may impair the temporal accuracy of responses by delaying perception-action coupling without severe influences on the spatial coupling of eye and hand during interceptive actions.